The Effect of Using Applications to Facilitate Medicine Purchase Amid the Covid-19 Pandemic - Eddy Soeryanto Soegoto; Nadia Tahiyyah Alifia; Tiara Salsabila; Cindy Nuke Mardika (Universitas Komputer Indonesia, 2022)
The purpose of this study was to determine the effect of technology on the pharmaceutical industry through applications to facilitate customers in purchasing medicinedru during the pandemic and to find out whether medicine sales during the Covid-19 pandemic affected the Indonesian economy. The method used in this research is descriptive method and qualitative method. with the technique of observing the results of writing related to the title and collecting field data. The research step is to look for references that refer to the title in order to get an overview for research on medicine sales applications that are more practical and in demand by the public in the Covid-19 pandemic condition. The results of this study indicate that medicine sales in the application are more desirable and have a significant increase. The increase in medicine sales was due to high consumer demand during a pandemic, people reduced outdoor activities and maintained their immune system to consume various medicine, vitamins, etc. From these results, it can be seen that the production of medicine sales is one sector that has increased with advances in technology, more and more people are choosing applications because it makes it easier for people to buy medicines, and medicine sales have an impact on improving the Indonesian economy during the COVID-19 pandemic.